PENGARUH NILAI TAMBAH PRODUKSI DAN JASA LOGISTIK PADA VOLUME EKSPOR PRODUK TEKSTIL DI JAWA TENGAH - Kurniani Kurniani; Yusmar Ardhi Hidayat; Achmad Zaenuddin; Suwardi Suwardi (Politeknik Negeri Semarang, 2019)
This research purposes to analyze the impact of production added value from textile industries and logistic service to textile export value in Central Java. The secondary data used are an export statistic and regional domestic product total, and logistics service between 2010 and 2017. The result shows that, first, production added value has negatively influence to textile export value. Second, logistic service has a positive effect on export value. It implies that textile export value may result in order demand. In addition, logistics service has the main role to boost up textile export.